UPAYA MENINGKATKAN HASIL BELAJAR AKIDAH AKHLAK MELALUI METODE ROLE PLAYING PADA SISWA KELAS VIII DI MTsN KOTA BOGOR - Maria Ulfah; Santi Lisnawati (Universitas Pakuan, 2019)
The purpose of this is to determine the improvement of students learning outcomes in class VIII MTsN Bogor, taught using the Role Playing method. The form of research used is Classroom Action Research. Presented in the third cycle, each cycle consists of 4 stages, planning, implementing, observing and refining. Data colection tecniques in the form of test questions with 10 items formed essays and indirect observation activities. The result of the study are obtained from the average value of student learning out comes cycle I was 52 with a percentage of 42,42% and increased in cycle II to 66,5% with a percentage of 78,78% and incerseted in cycle III to 66,5 with a percentage of 78.78%.